S. Baranova, K. Pletenko. Pragmatic and functional peculiarities of euphemisms for diseases, death and dying in the english mass-media discourse - S. Baranova; K. Pletenko (Philological Treatises, 2020)
The article describes euphemisation processes in English for the themes of diseases, death and dying on the materials of the mass-media discourse. It shows a detailed analysis of different lexical units of substituting nature to find out the reasons and causes of active language euphemisation. Nowadays euphemistic processes are wide spread, but the aim of their usage has changed from the times of ancient people which are thought to have been afraid of inexplicable things and using straightforward terms dealing with such subjects. Special attention is paid to finding the connections between euphemisms and people’s concepts and way of thinking. The analysis also stresses the timeless nature of this linguistic phenomenon, in which psychological, religious and social interdictions coexist.